Bubba and Beau go night-night - Appelt, Kathi, 1954-; Howard, Arthur (San Diego : Harcourt, 2003)
Even after a long day of running errands, baby Bubba and his puppy Beau are not ready for bedtime.
Ages 2-5.
Keywords: Babies -- Fiction; Dogs -- Fiction; Bedtime -- Fiction